Long-Term Effects of Shocks on New Opportunity and Necessity Entrepreneurship - Emilio Congregado; Frank M. Fossen; Nicola Rubino; David Troncoso (Institute of Labor Economics (IZA), 2024)
The dynamics of startup activity are crucial for job creation, innovation, and a competitive economy. Does regional firm formation exhibit hysteresis, such that shocks, including those induced by temporary policy interventions, have permanent effects? Due to the pronounced heterogeneity among new entrepreneurs, it is important to distinguish between those pulled by opportunity and those pushed by necessity. This distinction allows evaluating the long-term effects of policies aimed at stimulating opportunity entrepreneurship versus active labor-market policies supporting self-employment as a way out of unemployment. Based on 84 waves of quarterly microdata from the Spanish Labor Force Survey, we create time series of new opportunity and new necessity entrepreneurship for the 17 Spanish regions. To test whether exogenous shocks have long-run effects on firm formation, we apply a battery of panel data and time series unit root tests accounting for deterministic breaks. We also present results for the different Spanish regions and industrial sectors. We find that hysteresis is more widespread in new opportunity than in new necessity entrepreneurship, implying that shocks and temporary policies are more likely to shift opportunity than necessity entrepreneurship in the long run. Moreover, we document that the global Financial Crisis of 2008 changed the technology of firm formation out of opportunity, but not out of necessity. Our analysis opens the door to further research on the long-term effectiveness of a regional and sectoral policy mix of entrepreneurship promotion and active labor market policies.
Keywords: C32; E23; J24; L26; M13; 330; self-employment; opportunity entrepreneurship; necessity entrepreneurship; firm formation; hysteresis; stationarity; regions